CO60 dose and dose rate’s effects on Edamame Ryoko Jember variety’s growth and production - Eko Siswanto (Interdisciplinary Social Studies, 2024)
Edamame is a famous type of soybean plant in Japan, edamme is often also referred to as Japanese soybeans. The purpose of this study was to determine the Lethal Dose 20 (LD20) and lethal dose 50 (LD50) radiosensitivity measurements in ryoko varieties originating from Jember which have been irradiated by Cobalt60 gamma rays in BATAN, with 5 dose levels including, 100 Gy, 200 Gy, 300 Gy, 400 Gy, and 500 Gy with Gammacell220. Edamame plants of the Jember Local Varieties were treated with a radiation dose of 200 Gy and a dose of 400 Gy. The plant height, number of pods, and weight of 100 seeds were measured. The results of the T Test showed that the number of leaves of the radiated plants has a real difference compared to controls at observations of 28, 42, and 56 HST. The LD20 and LD50 values obtained indicate that genetically edemame plant of local varieties of jember have a high level of radiosensitivity because if plants are treated at doses exceeding 500 Gy, seed germination will be abnormal or damaged.